Marketing challenges in a turbulent business environment : proceedings of the 2014 Academy of Marketing Science (AMS) World Marketing Congress /: proceedings of the 2014 Academy of Marketing Science (AMS) World Marketing Congress. (2016) - Unknown
No abstract available